Prevention of Pegfilgrastim-Induced Bone Pain: A Phase III Double-Blind Placebo-Controlled Randomized Clinical Trial of the University of Rochester Cancer Center Clinical Community Oncology Program Research Base - Kirshner, Jeffrey J. (American Society of Clinical Oncology, 2012)
PURPOSE: Pegfilgrastim-induced bone pain is a significant clinical problem that may result in discontinuation of pegfilgrastim and lead to less effective chemotherapy dosing. Interventions for pegfilgrastim-induced bone pain are needed. PATIENTS AND METHODS: The University of Rochester Cancer Center Clinical Community Oncology Program Research Base randomly assigned 510 patients at 17 sites to receive either naproxen (500 mg two times per day) or placebo on the day of pegfilgrastim administration, continuing for 5 to 8 days after pegfilgrastim. Patients recorded pain severity (using a scale of 0 to 10) and duration in daily diaries. The primary outcome measure was the area under the curve (AUC) for pain for days 1 through 5. Secondary outcome measures included the identification of risk factors for the development of pain and response to naproxen. RESULTS: Patients' mean age was 55.6 years and 86% were female. Sixty-eight percent of patients had breast cancer and 10% had lung cancer. Pain reached its peak at 3 days for both groups. The mean AUC for pain was 7.71 for the placebo group and 6.04 for the naproxen group (P = .037). Naproxen reduced maximum pain from 3.40 to 2.59 (P = .005). Naproxen also reduced overall pain incidence from 71.3% to 61.1% (P = .020) and duration from 2.40 to 1.92 days (P = .009). The reduction in severe pain (> 5 on a scale of 1 to 10) from 27.0% to 19.2% was also significant (P = .048). Risk factors could not be identified to predict incidence, severity, or ability to prevent pegfilgrastim-induced bone pain. CONCLUSION: Our phase III randomized placebo-controlled clinical trial demonstrated that naproxen at a dose of 500 mg twice per day is effective in reducing the incidence and severity of pegfilgrastim-induced bone pain.